2021
DOI: 10.3389/fpsyt.2021.634346
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Reactivity and Family-Related Factors Associated With Self-Injurious Behavior in Adolescents Presenting to a Child and Adolescent Psychiatric Emergency Service

Abstract: Background: Adolescents presenting in a child and adolescent psychiatric emergency service show various psychiatric disturbances, most commonly suicidal ideation, suicide attempts, and non-suicidal self-injury (NSSI). It was postulated that especially disturbed emotion regulation contributes to self-injurious behavior of young people. This study aims to investigate the relevance of emotional reactivity (ER), as part of emotion regulation, during an acute crisis, how it relates to self-injurious behavior reinfo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 65 publications
(102 reference statements)
1
5
0
2
Order By: Relevance
“…Nascent mental problems in younger children may be characterized by diffuse symptoms, which may not crystallize as specific diagnoses until later in adolescence, causing this age group to primarily be described with more general ED terms, which did not yet point to a specific disorder. Self‐harm was more common in adolescents than in children in line with existing literature 33,36–38 and a recent study found that ED in particular contributed to self‐harm in adolescents 39 . Self‐harm is typically used as a way of coping with difficult thoughts or feelings 33,37 and may be a deliberate strategy of regulating emotions.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Nascent mental problems in younger children may be characterized by diffuse symptoms, which may not crystallize as specific diagnoses until later in adolescence, causing this age group to primarily be described with more general ED terms, which did not yet point to a specific disorder. Self‐harm was more common in adolescents than in children in line with existing literature 33,36–38 and a recent study found that ED in particular contributed to self‐harm in adolescents 39 . Self‐harm is typically used as a way of coping with difficult thoughts or feelings 33,37 and may be a deliberate strategy of regulating emotions.…”
Section: Discussionsupporting
confidence: 73%
“…Self-harm was more common in adolescents than in children in line with existing literature 33,[36][37][38] and a recent study found that ED in particular contributed to self-harm in adolescents. 39 Self-harm is typically used as a way of coping with difficult thoughts or feelings 33,37 and may be a deliberate strategy of regulating emotions. Risk factors for self-harm include adverse childhood environment and experiences, maladaptive parenting, and childhood maltreatment, 38 which may lead to stress reactions or adjustment disorders, possibly explaining that these were the most frequent diagnoses in children with self-harm.…”
Section: Emotion Recognitionmentioning
confidence: 99%
“…For socioeconomic factors, the influence of the following factors was observed: being an only child; 14,26,31,34 low economic situation; 6,18,36,49,52,83,88 low education; 15,63 and having an employment relationship. 29 As for family factors, the following stand out: low parental education; 15,25,36 conflicts with parents or between siblings; 13,21,31,34,39,45,48,52,56,64,79,82,87,92 witnessing domestic violence; 12,32,39 separated parents; 13,18,32,39,60,64 absence/excessive presence of parents; 14,17,28,35,39,86 self-inflicted violence in the family; 18,53,84,…”
Section: Methodsmentioning
confidence: 99%
“…In a previous publication a significant positive correlation between patients' ERS sensitivity score and the occurrence of NSSI within the last year was found and a correlation between the ERS and different types of reinforcement as a motivating factor for NSSI was detected (25). In order to explain the emergence and maintenance of NSSI, Hasking et al have introduced the Cognitive-Emotional Model of NSSI.…”
Section: Introductionmentioning
confidence: 99%